Influence of Calcium Addition on Growth of Highly Purified Syntrophic Cultures Degrading Long-Chain Fatty Acids - Roy, Francis (1985)
Two highly purified syntrophic associations resulting in acetogenesis from stearate (SM) and oleate (OM) were obtained from the sludges of a sewage digestor. In both cases, Methanospirillum hungatei together with short, motile, gram-negative, nonfluorescent rods morphologically similar to Syntrophomonas wolfei were identified by microscopic examination. Besides growing on volatile fatty acids (butyrate through caproate), both cultures grew on oleate (C(18:1)) and numerous even-numbered, saturated long-chain fatty acids (LCFA [decanoate through stearate]). In addition, during growth on LCFA, supplementation of the culture media with calcium chloride was an absolute requirement. The sole difference between the associations was observed when SM and OM cultures were transferred from a stearate to an oleate medium. The SM culture needed 10 days before starting to degrade oleate, whereas the OM culture grew immediately, but the OM culture also grew immediately when transferred to stearate medium. Saturated LCFA degradation occurred in the presence of equinormal amounts of calcium (fatty acid/Ca ratio, 2). On the other hand, OM degradation only took place in the presence of an equimolar amount of calcium (fatty acid/Ca ratio, 1). These observations are discussed by considering the solubility constants of LCFA as calcium salts and the toxicity of the free acids against microorganisms.